Ecological features of wolves (Canis Lupus) Central Kazakhstan - Қартбаева, Г.Т. (Fundamental and Experimental Biology, 2015)
This article discusses the current state of wolves in Central Kazakhstan: biological, ecological features and size. Analyzed population dynamics and distribution by region Karkaraly Bakhty, Ulitau. The comparative characteristic parameters morfofiziziolgichesih wolves in Kazakhstan and Central Kazakhstan. Identified their main habitat.